A Letter from the Editor-in-Chief - Kudish, Bryan (Columbia Undergraduate Research Journal, 2014)
It is my pleasure to introduce to you the first volume of the Columbia Undergraduate Research Journal, an interdisciplinary publication that serves as a platform for undergraduates from all over the world to display the fruits of their academic investigations. The diversity of our authors is matched only by that of their subject matters, which range anywhere from biomedical engineering to political science and astrophysics. One thing is certain: our organization is privileged to showcase the work of this incredible set of individuals. Before each research piece, you will find a concise commentary written by a member of our editorial staff that places the author’s arguments and findings in the context of ongoing conversations in his/her field and related disciplines in order to more effectively communicate the significance of the research to any passing reader. With this initial volume of our journal, we lead the battle against negative the stereotypes attached to undergraduate journalism by seeking to adopt the practices of premier research publications, emphasizing ethically sound review policies and overall professionalism in our interactions with our authors. As we launch our website, we look forward to initiating a double blind peer review process, and to making our content freely available through our open access interface. We are an organization dedicated to our brilliant contributors, our tireless editorial staff, and of course you, the reader, from whom the entire process and presentation of research derives its significance. Best regards, Bryan Kudisch, Editor-in-Chief